THEORETICAL RESEARCH ON THE DEVELOPMENT OF ENTERPRISE SCIENCE AND TECHNOLOGY INNOVATION IN THE CONTEXT OF NEW QUALITY PRODUCTIVE FORCES - Qiao Jun; Reynaldo Gacho Segumpan (Journal of Islamic, Social, Economics and Development, 2024)
The Central Economic Work Conference at the end of 2023 listed "leading the construction of a modernized industrial system with scientific and technological innovation" as the first of the nine critical tasks. It emphasized that "scientific and technological innovation should be used to promote industrial innovation, in particular, subversive and cutting-edge technologies, to give rise to new industries, new modes, and new momentum, and to develop new quality productive forces." Not long ago, General Secretary Xi Jinping emphasized in the eleventh collective study of the Political Bureau of the Communist Party of China (CPC) Central Committee that "scientific and technological innovation can give rise to new industries, new modes, and new momentum, which is the core element of developing new productivity." He also said that "we should timely apply scientific and technological innovation to specific industries and industrial chains, transform and upgrade traditional industries, cultivate and expand new industries, cultivate and grow new layout and build future industries in order to improve the modernized industrial system." This article centers on the relationship between new quality productive forces and enterprise innovation, aiming to deeply explore the role of new quality productive forces in promoting enterprise innovation and its internal mechanism. Firstly, the article will start from the concept and characteristics of the new quality productive forces, and analyze its differences and advantages with the traditional productivity. Secondly, through empirical research and case studies, it will elaborate on how the new quality productive forces drive enterprise innovation activities and promote technological progress and product upgrading. Finally, from the perspectives of organizational structure and talent motivation, it discusses how enterprises should effectively integrate the new quality productive forces to stimulate innovation vitality and enhance competitive strength.